Effect of Solid-State Fermentation (SSF) on the Antioxidant and Hypoglycemic Activities of Jackfruit (Artocarpus Heterophyllus Lam.) By-Products using Aspergillus Niger, Aspergillus Oryzae and Rhizopus Oryzae - Gnoumou, Edouard; Kongpichitchoke , Teeradate; Jose, Ashika (Trends in Sciences, 2023)
The objective of this experiment was to study the effect of Solid-State Fermentation (SSF) on jackfruit by-products using filamentous fungi. Rags from a ripen jackfruit were fermented for 5, 10 and 15 days by Aspergillus niger, Aspergillus oryzae and Rhizopus oryzae at 30 °C. Then the bioactive compounds were extracted using methanol. Total phenolic content, total flavonoid content, antioxidant activity and hypoglycemic activity of each liquid extract were estimated. The results showed significant increase and improvement in the samples in which SSF was applied. The highest total phenolic contents were found in fermented products with A. niger and R. oryzae with an average of 14.16 mg GAE/g D.S which was almost 3 times over the concentration found in unfermented products (4.83 mg GAE/g D.S). The same fermented products showed a significant increase in total flavonoid content which was 2 times higher than unfermented products with an average of 31.79 mg QuE/g D.S for fermented products and 15.08 for unfermented. The antioxidant activity was correlated to the total phenolic and flavonoid contents with the highest activity of around 76 % found in fermented products against 55 % for the unfermented ones. Finally, hypoglycemic activity was also found to be higher in fermented products than the unfermented with the best activity obtained in 5-days fermented product with A. oryzae (35.62 %) which was 8 times higher than non-fermented products (4.52 %). The present study showed that Solid-State Fermentation has a great potentiality to improve and enhance antioxidant and hypoglycemic activities of plant by-products. HIGHLIGHTS SSF improved the Antioxidant and hypoglycemic properties of jackfruit rags niger and R. oryzae had better capacity in improving the antioxidant activity Phenolic Content, Flavonoid Content and Antioxidant Activity were correlated Better hypoglycemic activity was seen in fermented products with oryzae oryzae could produce a new bioactive compound with high hypoglycemic activity GRAPHICAL ABSTRACT